СОВРЕМЕННОЕ СОСТОЯНИЕ ИННОВАЦИОННОГО ПРЕДПРИНИМАТЕЛЬСТВА В РЕСПУБЛИКЕ КАЗАХСТАН - Кулекеева, А. (Journal of Economic Research & Business Administration, 2016)
To take the deserving place in the world market and use his advantages for development of innovative enterprise in Republic of Kazakhstan, it is important to follow international experience. In the conditions of quickly changing economic environment, to produce strategy in area of innovative development, and on this basis are increases of competitiveness of the Kazakhstan economy on the whole and industrial production, first of all.